Low power hardware design and its mathematical modeling for fast‐exact geolocalization system in wireless networks. (22nd February 2022) - zaidi, Monji; Bouazzi, Imen; Al‐Rayif, Mohammed Ibrahim; Shamim, Mohammed Zubair Mohammed; Usman, Mohammed
Summary: A significant goal in achieving position calculation is to reduce and simplify the instructions that the Mobile Station (MS) has to accomplish in the location determination algorithm. Standard techniques widely used in many applications can be classified into Received Signal Strength Indicator (RSSI), Angle of Arrival (AoA), Time Difference of Arrival (TDoA), and Time of Arrival (ToA). However, all are almost determined by the standard trigonometric complex computation methods that are usually implemented in software where the complexity is considerable. The development of a simple and efficient technique for MS location estimation is the main objective of this paper. To design a modern hardware‐oriented algorithm, a new approach using simple Add‐and‐Shift operations in the computation is proposed and it can be implemented in a hardware target. In order to accelerate the geopositioning process, the Coordinate Rotation Digital Computer (CORDIC) algorithm has been used in this proposal. The proposed algorithm is simpler and faster than conventional ones; thus, complexity in terms of time, power consumption, and chip area has been reduced. Therefore, the algorithm is suitable for applications with limited computational and power resources. Based on comparisons with the state‐of‐the‐art algorithms, it is concluded that the proposed technique is more exact and less complex. Abstract : Hardware circuit for exact geolocalization in wireless network is designed. Proposed localization algorithm is based on Coordinate Rotation Digital Computer‐Time of Arrival (CORDIC‐ToA) combination. Current proposal is governed by the hardware implementation in order to alleviate its cost, which most of the localization systems suffer from.